1975
DOI: 10.3109/17453677508989287
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte Mitosis in the Articular Cartilage of Femoral Heads with Various Diseases

Abstract: Autoradiographic studies using thymidine-3H reveal the mitosis of chondrocytes in degenerated joints, i.e. joints having secondary osteoarthritis or aseptic necrosis of the femoral head. The findings obtained provide additional support for the recent investigations regarding chondrocyte mitosis in primary osteoarthritic cartilage. Histologic and histochemical examinations suggest that a loss of glycosaminoglycans in the matrix is evidence for conversion of chondrocyte activity to mitosis which occurs, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The proliferation of chondrocytes in OA cartilage is the accepted hypothesis for the formation of the ''clones'' (Mankin, 1962a,b;Telhag, 1972Telhag, , 1973Rothwell, 1973;Hirotani and Ito, 1975;Havdrup, 1978). All data supporting this hypothesis have been based on the incorporation of 3 H-Tymidine in the OA chondrocytes or on the presence of two nuclei within the same lacuna (Lee et al, 1993).…”
Section: Results and Discussion Phenotype Variability Of Chondrocytesmentioning
confidence: 99%
“…The proliferation of chondrocytes in OA cartilage is the accepted hypothesis for the formation of the ''clones'' (Mankin, 1962a,b;Telhag, 1972Telhag, , 1973Rothwell, 1973;Hirotani and Ito, 1975;Havdrup, 1978). All data supporting this hypothesis have been based on the incorporation of 3 H-Tymidine in the OA chondrocytes or on the presence of two nuclei within the same lacuna (Lee et al, 1993).…”
Section: Results and Discussion Phenotype Variability Of Chondrocytesmentioning
confidence: 99%
“…The requirement of human chondrocytes for human rather than fetal bovine serum has been shown in previous studies (23). Autoradiographs have repeatedly failed to reveal incorporation of thymidine into normal adult human or rabbit articular cartilage (24,25). Our observation that label-ing did occur, when 3H-Tdr that had high specific activity was used for a long (19-hour) incubation period, suggests that some of these cells already are engaged in or are more readily induced to enter into DNA synthesis than is ordinarily perceived.…”
Section: Resultsmentioning
confidence: 81%
“…Previous studies have demonstrated enhanced sulfate incorporation by chondrocyte clusters in fibrillated patellae, and this was related to the rate of chondrocyte proliferation (21,44). While chondrocytes in normal cartilage are generally considered to be mitotically dormant, convincing metabolic (35,47,50) and autoradiographic (45,46,48,49) evidence has shown that chondrocytes can switch to a reactive mitotic proliferation under traumatic or degenerative conditions. That all the chondrocytes within these clusters originate from the one original progenitor cell in the chondron, and hence form a true "clone," has yet to be established.…”
Section: Discussionmentioning
confidence: 96%
“…It is characterized in both spontaneous and experimentally induced disease by marked alterations in matrix histochemistry (20)(21)(22)(23)(24)(25)(26)(27) and ultrastructure (28-34), biochemical composition (3541), and cellular metabolism (21,35,(42)(43)(44). Variable rates of chondrocyte necrosis and reactive mitotic proliferation have also been reported (35,(45)(46)(47)(48)(49)(50). In this study, we focused our attention on the chondrocyte and its pericellular microenvironment, following the application of chondron extraction techniques to normal and osteoarthritic human and canine cartilage.…”
Section: Discussionmentioning
confidence: 99%